Antifungal Agents Based on Chitosan Oligomers, ε-polylysine and Streptomyces spp. Secondary Metabolites against Three Botryosphaeriaceae Species - Laura Buzón-Durán; Jesús Martín-Gil; Eduardo Pérez-Lebeña; David Ruano-Rosa; José L. Revuelta; José Casanova-Gascón; M. Carmen Ramos-Sánchez; Pablo Martín-Ramos (MDPI AG, 2019)
Grapevine trunk diseases (GTDs) are a major threat to the wine and grape industry. The aim of the study was to investigate the antifungal activity against Neofusicoccum parvum, Diplodia seriata, and Botryosphaeria dothidea of ε-polylysine, chitosan oligomers, their conjugates, Streptomyces rochei and S. lavendofoliae culture filtrates, and their binary mixtures with chitosan oligomers. In vitro mycelial growth inhibition tests suggest that the efficacy of these treatments, in particular those based on ε-polylysine and ε-polylysine:chitosan oligomers 1:1 w/w conjugate, against the three Botryosphaeriaceae species would be comparable to or higher than that of conventional synthetic fungicides. In the case of ε-polylysine, EC90 values as low as 227, 26.9, and 22.5 µg·mL−1 were obtained for N. parvum, D. seriata, and B. dothidea, respectively. Although the efficacy of the conjugate was slightly lower, with EC90 values of 507.5, 580.2, and 497.4 µg·mL−1, respectively, it may represent a more cost-effective option to the utilization of pure ε-polylysine. The proposed treatments may offer a viable and sustainable alternative for controlling GTDs.